Adsorption of anionic azo dyes from aqueous solution on cationic gemini surfactant-modified flax shives: Synchrotron infrared, optimization and modeling studies. (20th January 2018) - Wang, Wenxia; Huang, Guohe; An, Chunjiang; Zhao, Shan; Chen, Xiujuan; Zhang, Peng
Abstract: There is an emerging interest in using biomass waste for environmental applications. In this study, the flax shives modified by cationic gemini surfactant (MFS) were used for the removal of anionic azo dyes from aqueous solution. Response surface methodology (RSM) was used to determine the optimal modification conditions. The surface of MFS was characterized by synchrotron infrared and SEM analysis. The equilibrium and kinetic analysis for the adsorption of Acid Orange 7 (AO-7), Acid Red 18 (AR-18) and Acid Black 1 (AB-1) on MFS was conducted. The adsorption equilibrium data were well fit by the Langmuir model. The adsorption process followed the pseudo-second-order and Elovich models. Thermodynamic studies indicated that the adsorption of three anionic azo dyes was spontaneous and exothermic. The adsorption of acidic azo dyes on MFS was influenced by temperature, initial pH, MFS dosage and ionic strength. The interactions of these four factors were further investigated through a two-level full factorial design. The results can help better understand the transport behaviors of organic pollutants at biomass adsorbent-water interface. It also presents the potential of MFS as a suitable adsorbent for the removal of anionic azo dyes from wastewater. Highlights: Gemini-surfactant modified flax shives for removing anionic azo dyes. The equilibrium and kinetic studies for the adsorption of anionic azo dyes. New insights from synchrotron IR, optimization and interaction analysis. Potential as biomass adsorbent for the removal of dyes from wastewater. The migration patterns of dye pollutants at flax shive-water interface.